Synthesis and structure determination of s,s′-(Naphthalen-2-ylmethyl sulfanyl (1-p-tolyl-ethylidene) hydrazine - How, Fiona Ni Foong; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim; Watkins, David J. (SpringerLink, 2009)
S,S′-(Naphthalen-2-ylmethyl sulfanyl (1-p-tolyl-ethylidene) hydrazine (SNM4MA) was prepared by the condensation of S-napthalen-2-ylmethyldithiocarbazate (SNMDTC) and 4-methylacetophenone. Yellow needles of SNM4MA were obtained upon slow evaporation of a 50:50 mixture of acetonitrile and DMSO over a period of weeks. The compound crystallizes in the monoclinic system with the space group C 2/c and Z = 4. The unit cell parameters are a = 7.0221(2) Å, b = 22.8428(6) Å, c = 23.5127(6) Å with β = 94.0222(13)°. Single crystal X-ray analysis shows that the molecule has crystallographic two-fold rotational symmetry coincident with the S–S bond. The title compound exists as a trans–cis conformer in which the naphthalene group is trans with respect to the thione sulfur while the benzyl group adopts a cis geometry. 13C and 1H spectra confirm that the dimeric nature is retained in DMSO solution.